Effect on Growth and Economics in Maize (Zea mays L.) Based Intercropping Systems - Kithan, Lowrence; Longkumer, L. Tongpang (International Journal of Economic Plants, 2016)
A study was conducted on the effect on growth and economics in maize (Zea mays L.) based intercropping systems at the experimental farm of School of Agricultural Sciences and Rural Development (SASRD) Nagaland University, Medziphema Campus, Nagaland under rainfed condition during 2015 and 2016. The treatments comprised of different row ratios i.e. (1:1), (1:2), (2:1) and (2:2) respectively of maize intercropped with perilla, sesame, ricebean and soybean along with sole crops of maize, perilla, sesame, ricebean and soybean. The experiment was laid in RBD with 3 replications and 21 treatments. Among the different sole crops sole maize performed better with respect to growth and yield. Among the different intercropping systems paired rows (2:2) ratios of maize + soybean performed significantly better in terms of yield (1564.21 kg ha-1, 1567.10 kg ha-1, 1565.65 kg ha-1). As for economics, paired rows (2:2) ratios of maize + soybean proved superior to all other treatments in LER (1.78, 1.78), net return (INR 1,42,612.6, INR 1,44,779.4), gross return (INR 1,72,612.6, INR 1,74,779.4) and B:C ratio (4.75 and 4.82).